Life and sensibility of biological matter in the philosophy of Xavier Zubiri - Catalán, Jr., Marcos Louis (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
The present essay discusses Zubiri’s ideas about biological matter, which matter, the essence of material substantivities, gives of itself through its potentiality of systematization. An animalis a dynamically stable and reversible biological structure, and its life and sensibility are systemic properties. They are functional combinations emerging from the respective activities of the component organic molecules of an animal. Life is not a force, but a dominant principle orienting molecular actions. As for the animal’s sensibility, Zubiri analyzes it on three levels, namely, the sensing process, habitude, and constitutive structures. The indivisible sensing process consists of arousal, tonic modification, and response as constitutive moments. Habitude, the manner of dealing with things, underlies the sensing process, and the habitude specific to the animal is sensibility. The corresponding formality is the formality of mere stimulus, i.e., the animal apprehends the stimulus only as a sign of response and nothing more. The animal’s sentient process and habitude, in turn, are made possible by its constitutive structures, specifically, its nervous system. Its morphological complexification can be understood as an advancein formalization: The greater is the degree of formalization, the more varied are the perceptions (arousal), affects (tonic modification), and possible responses available to the animal. But no matter how highly formalized its nervous system may be, the animal will never cease to apprehend something under the formality of mere stimulus.